PHBS Cuci Tangan Mempengaruhi Angka Kejadian Diare: Handwashing PHBS Affects the Incidence of Diarrhea. - Tiara Dwi Pebriani; Emi Yuliza; Nurul Syifah (MPI Press, 2022)
Background: Handwashing as a part of healthy and hygienic behavior (PHBS) significantly affects the incidence of diarrhea in infants (0-1 years old), with mothers playing a crucial role in this practice. Objective: This study aims to determine the impact of PHBS (Healthy and Hygienic Behavior) handwashing through virtual WhatsApp videos on the incidence of diarrhea in infants (0-1 years old) in the Gandoang Subdistrict, Bogor Regency in 2021. Method: This research is a pre-experimental study using the One Group Pretest-Posttest research design. The population in this study consists of mothers with infants (0-1 years old) in the Gandoang Subdistrict, Bogor, in 2021. The sample size is 20 respondents, selected using the Total Sampling method. Data analysis was conducted using the McNemar test. Results: Based on the research results, before receiving PHBS handwashing education, more than 3 episodes of diarrhea were reported by 12 respondents (60.0%). After receiving PHBS handwashing education, more than 3 episodes of diarrhea were reported by 3 respondents (15.0%). The statistical test results showed a p-value of 0.004, which is < 0.05. Conclusion: There is an influence of PHBS (Healthy and Hygienic Behavior) handwashing through virtual WhatsApp videos on the incidence of diarrhea in infants (0-1 years old) in the Gandoang Subdistrict, Bogor Regency in 2021.